Mechanisms and abnormalities in business valuation of football enterprises - Cieplucha, Mateusz (Quality in Sport, 2016)
The paper shows in synthetic way a process and irregularities in the football business valuation. It has been shown selected valuation methods, their strengths, weaknesses and limitations. Paper also indicate the factors on which depends the process of clubs evaluations. Further part of article discusses examples of ways used by decision-makers and accountants to manipulate the financial reporting units that reduce transparency and legitimacy of valuation. The following part of the study describes the conditions of evaluation and assessment of enterprises of football in relation to their specific business evident. The aim of the study was to present ambiguity and difficulty evaluating sports business. Football business has wide range of features marked by quality factors. This characteristic affects so significant dimension to design differences among book value and market value. The research material used in the study is a review of the literature and simulation model of football business valuation based on ratio analysis, P/E and P/BV indicators.